PEMBELAJARAN DARING DI SMA YAYASAN WANITA KERETA API (YWKA) KERTA PATI PALEMBANG PADA MASA PANDEMIK COVID-19 - Sunardi, Sunardi (Epsilon: Jurnal Pendidikan Matematika, 2021)
Abstract: This study was to determine the obstacles experienced by students, mathematics teachers and leadership elements of SMA YWKA Kertapati Palembang in carrying out online and offline during the covid -19 pandemic in the even semester of the 2020/2021 school year. The research method used is a qualitative descriptive method, with mathematics teachers, homeroom teachers, and vice principals in the field of curriculum, as well as students as respondents. The instrument in collecting research data uses: (1) 4-question essay test, to determine learning outcomes of online learning implementation and students' ability to solve equations and quadratic functions, online or offline, (2) Interviews, (3) Questionnaires given to respondents online via google form. Interviews were conducted with the vice principal in the field of curriculum, homeroom teachers, mathematics teachers and 12 students. The results obtained from the ability test to solve questions with an average value of 70.03. The results obtained based on interviews with school leaders and homeroom teachers are that the online implementation has been carried out, but it is still not optimal because there are students who do not have Android phones. The results of interviews with teachers for implementing learning also stated that online was already running, but teachers still had to come to school to serve students who did not have mobile phones. Then for the student questionnaire, it was found that online learning was fun even though there were still obstacles.